Ender's shadow - Card, Orson Scott (New York : Tor, 2000)
Bean must overcome his past and prove to the recruiters at the Battle School that he can help save the planet from an alien invasion.
"A Tom Doherty Associates book."
Adult
Adult
Keywords: Imaginary wars and battles -- Fiction; Life on other planets -- Fiction; Life on other planets -- Fiction; Science fiction; Space warfare -- Fiction; Science fiction